Retention of posterior resin bonded fixed dental prostheses with different designs after chewing simulation. (November 2021) - Tagami, Atsuko; Chaar, M. Sad; Wille, Sebastian; Tagami, Junji; Kern, Matthias
Abstract: The aim of this study was to evaluate the effect of different preparation and framework designs on the retention of posterior resin bonded fixed dental prostheses (RBFDPs) made from monolithic zirconia ceramic. Forty-eight caries-free upper premolars and forty-eight upper third molars were used in this study. The teeth were randomly divided into six main groups (n = 8 each) according to the preparation design of two-retainer RBFDPs: narrow or wide rest, combined with 0, 1 or 2 retainer wings. All RBFDPs were milled from monolithic zirconia ( KATANA Zirconia ML). They were bonded using Panavia V5 with its corresponding primer, and underwent thermodynamic loading (98 N, 1, 200, 000 cycles). Retention was evaluated for the surviving RBFDPs in a universal testing machine by means of a debonding test. Failure modes were evaluated using a light microscope. Data was statistically analyzed by Kruskal-Shapiro-Wilk followed by Mann-Whitney with Bonferroni correction for multiple testing. The survival rates after the chewing simulation were 75% (group narrow rest/no retainer wing), 62.5% (group wide rest/no retainer wing) and 100% (the other groups). The mean retention ranged from 31 N to 766 N. Designs with two retainer wings showed significantly higher bond strength than the other designs (p ≤ 0.05). The rest width did not show a significant effect on the retention. Posterior RBFDPs with a modified design (occlusal rest and two retainer wings) exhibited promising durability and retention. Designs with two additional retainer wings should be preferred over designs with one or no retainer wing, irrespectively of the rest width.